PERAN MULTIMEDIA INTERAKTIF PEMBELAJARAN MEMBACA AL-QUR’AN BERDASARKAN ILMU TAJWID DENGAN METODE JOYFUL LEARNING DI MI MATHLA’UL ANWAR MARGOSARI: Indonesia - Laili Nur Baiti; Tuti Puspitasari; Ikhsan Mustofa (Al-Ibda: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2022)
Abstract As for some of the problems that the researchers found at Madrasah Ibtidaiyah Mathla ul Anwar (MIMA) Margosari, namely the lack of interest and lack of reading law and makhroj. This resulted in many students who do not understand the reading of the Koran is good and correct. The purpose of this study was to determine the role of interactive multimedia in learning to read the Qur'an with the joyfull learning method. This study used a qualitative approach. The data collection technique in this study was through observation, documentation and interviews because with this method, detailed data could be obtained starting and activities. tedious learning to the learning outcomes of the role of media in learning. The sample of this study was 52 large class students from class 5-6 MIMathla'ul Anwar Margosan using cluster random sampling technique. The results obtained from this research are that students are more enthusiastic to learn and are motivated to learn tajwid and understand the law of reading and are able to apply makhraj on reading the Qur'an. Keywords: The role of interactive multimedia, the Qur'an, Tajweed science, joyful learning